Evaluation of minimum service standard achievement in maternal health services using a logic model - Rangi Media Febriza; Rumita Ena Sari; Arnild Augina Mekarisce; Adila Solida; Vinna Rahayu Ningsih (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Maternal health services are one of the Minimum Service Standards (MSS) indicators in the health sector that must achieve a 100% target. However, the achievement of maternal health services in Muaro Jambi Regency in 2025 reached only 61.96%, while the achievement was 90.93% (496 of 546 targeted pregnant women). In addition, antenatal care coverage remained below the expected target, with K1 coverage at 67.40%, K4 at 61.36%, and K6 at 50.37%. These findings indicate that maternal health service implementation has not been optimal. Therefore, an evaluation using the Logic Model framework, consisting of input, activities, and output, was conducted. Purpose: To evaluate the achievement of minimum service standard health performance indicators in maternal health services. Method: This study employed a qualitative research design using the Logic Model evaluation framework. Informants consisted of the Head of the Community health center, the Maternal and Child Health (MCH) Program Coordinator, midwives, village midwives, and pregnant women selected through purposive sampling. Data were collected through in-depth interviews, observations, and document reviews. Data were analyzed using the Miles and Huberman interactive analysis model, including data reduction, data display, and conclusion drawing. Results: The input component generally supported the implementation of maternal health services. However, several challenges were identified, including suboptimal workload distribution among healthcare personnel , limited MCH clinic facilities, and delays in the distribution of Maternal and Child Health (MCH Handbooks). The activities component showed that all maternal health service activities had been implemented according to established standards. Nevertheless, delays in antenatal visits, low continuity of K1–K6 antenatal care visits, inadequate monitoring of iron tablet compliance, and delayed MCH Handbooks distribution affected service documentation and health education. The output component indicated that the achievement of maternal health service MSS indicators had not yet reached the national target of 100%. Conclusion: The achievement of maternal health service MSS indicators has not yet met the expected target. This was influenced by suboptimal workload distribution among healthcare personnel , delays in MCH Handbooks distribution, and inadequate continuity of antenatal care visits through K6. Suggestion: Strengthening the community health center had not, optimizing resource management, and improving follow-up and monitoring of pregnant women are necessary to improve the achievement of maternal health service MSS indicators.